Feline Cryptococcosis due to Cryptococcus gattii VGII (Recently Renamed as C. deuterogattii) in an FIV-Positive Cat With Demodicosis From Manaus, Central Amazon, Brazil - Nayara de Fátima Lazameth-Diniz; Adriana Oliveira da Silva Queiroz; Flávia da Silva Fernandes; João Fernando Vieira Ennes; Naira Sulany Oliveira de Sousa; Ana Claudia Alves Cortez; Jacqueline da Silva Batista; Eveleise Samira Martins Canto; Kátia Santana Cruz; Ani Beatriz Jackisch-Matsuura; Ormezinda Celeste Cristo Fernandes; Suanni Lemos de Andrade; et al. (Case Reports in Veterinary Medicine)
This case report documents the diagnosis and successful treatment of cryptococcosis caused by Cryptococcus gattii VGII in a 20-month-old male domestic shorthair cat from Manaus, Brazil, which was concurrently infected with feline immunodeficiency virus (FIV) and diagnosed with demodicosis. The cat presented with mucopurulent nasal discharge, cutaneous lesions on the neck, and a subcutaneous mass between the shoulder blades. Laboratory investigations, including fine-needle aspiration cytology, fungal culture, and PCR-RFLP genotyping, confirmed the presence of C. gattii VGII. The cat was treated with fluconazole (10 mg/kg/day) and topical fluralaner–moxidectin, resulting in complete clinical resolution of all lesions and associated symptoms. This report underscores the significance of considering cryptococcosis as a differential diagnosis in immunocompromised cats presenting with cutaneous or respiratory symptoms. Additionally, it highlights the importance of recognizing the Amazon region as an area of environmental prevalence of C. gattii VGII, reinforcing the need for awareness regarding its impact on animal health.